Gender quotas in development programming: Null results from a field experiment in Congo - Peter van der Windt; Macartan Humphreys; Raul Sanchez de la Sierra (Journal of Development Economics, 2018)
We examine whether gender quotas introduced by development agencies empower women. As part of a development program, an international organization created community management committees in 661 villages to oversee village level program expenditures. In a randomly selected half of these villages the organization required the committees to have gender parity. Using data on project choice from all participating villages, data on decision making in a later development project (105 villages), and data on citizen attitudes (200 villages), we find no evidence that gender parity requirements empower women. We discuss potential reasons for the null result, including weakness of these social interventions in terms of the engagement they generate, their time horizon, and the weak delegation of responsibilities.
doi:10.7910/DVN/BSASJR
Keywords: D72; P48; D02; O17; 330; Gender quotas; Experimental methods; Development aid; Political attitudes and behavior